Art and Innovation at International Health Promotion Conferences - Ayele, Christa (2021)
Scientific conferences are a constant fixture in most academic and professional fields. While conferences began in the mid-1800s as a platform for the exchange of ideas, in reality, the majority of scientific conferences follow a predictable, didactic format that is aligned with Northern/Western conceptions of learning and knowledge hierarchy. Area ?experts? are provided a platform to share their knowledge, and the audience is thought of as empty vessels receiving deposits of this knowledge. Rarely is this model brought into question. This chapter describes conference sessions organized by the Student and Early Career Network of the International Union for Health Promotion and Education that turned this model upside down and used art as a means to dialogue and exchange with participants on important health promotion topics. In this chapter, we demonstrate how these sessions stimulated engagement and exchange while seeking to honor multiple voices and ways of knowing.